Investigation of the pyrolysis behaviour of hybrid filter media for needle-punched nonwoven bag filters. (25th February 2017) - Nie, Xueli; Shen, Henggen; Wang, Yinghui; Zhou, Liuke; Liu, Xingcheng; Fang, Min
Highlights: Py-GC–MS was proposed analyzing the contents of PTFE for hybrid filter media. The pyrolysis temperature was 750 °C with the most abundant species identified. The contents of order for PTFE were found with hybrid filter media B, A and C. Abstract: Hybrid polymer fibre filter media are critical to the effectiveness of needle-punched nonwoven bag filters. We investigated the pyrolytic behaviour of hybrid filter media to analyze the contents of the components. The pyrolytic behaviour was investigated using pyrolysis-gas chromatography–mass spectrometry (Py-GC–MS). Pyrolysates were directly injected for GC–MS analysis. In total, 19, 22 and 23 compounds were identified with contents varying from 0.29% to 78.30%, 0.14% to 78.75% and 0.34% to 70.96% for hybrid filter media A, B and C, respectively. A large number of monocyclic and polycyclic aromatic compounds were formed when the pyrolysis temperature was greater than 650 °C. The contents of aromatic hydrocarbons increased with increasing temperature. In addition to the aromatic compounds, monomeric and diploid tetrafluoroethylene were produced. The contents of the fluorochemical for the hybrid filter media A, B and C were 46.04%, 52.60% and 1.85%, respectively, when the pyrolysis temperature was 750 °C. A pyrolysis mechanism for the hybrid filter media was proposed based on the determined pyrolysates. The investigation results provide useful information for understanding the thermal properties of hybrid filter media. The contents of PTFE were quantitatively analysed to assess the influence of the hybrid filter media on the abrasion resistances.